The Melding of Drug Screening Platforms for Melanoma - Couto, Gabriela Klein; Segatto, Natália Vieira; Oliveira, Thaís Larré; Seixas, Fabiana Kömmling; Schachtschneider, Kyle M.; Collares, Tiago (Frontiers in Oncology, 2019)
The global incidence of cancer is rapidly rising and remains a leading cause of death worldwide, highlighting the need for continued research focused on development of novel treatment strategies. According to the World Health Organization (WHO), about 8.8 million people die of cancer each year, with 600.000 new cancer cases expected in Brazil in 2018. This is partially due to the increased incidence of melanoma in recent years, which represents one of the fastest growing forms of cancer, with advanced metastatic forms carrying high mortality rates due to the development of drug resistance. Although early-stage melanoma can be treated with surgery, advanced (metastatic) disease is difficult to cure and treatment options are unsatisfactory, highlighting the urgent need for novel treatment strategies. Nowadays research into new pharmacological treatments takes place in several ways in order to adhere to the 3R principle: "reduction, replacement, and refinement" of animal use in research. In silico techniques, such as molecular docking, represent a necessary first step of the screening process. These approaches provide a cost effective approach to better identify potential drug candidates; however, more comprehensive software is required for this approach to be utilized to its full potential. In vitro approaches utilizing melanoma cell lines represent the next step in the drug development pipeline, with the need to mimic the tumor microenvironment in vitro prompting development of novel 3D culture systems to reduce the limitations of traditional in vitro tests. The final step in this process consists of testing candidate drugs in in vivo settings, for example through the use of genetically engineered mouse models or patient-derived xenografts. The purpose of this review is to investigate approaches utilized for screening of novel melanoma treatments over the past few decades in order to investigate the importance of utilizing a combination of in silico, in vitro, and in vivo screening strategies for melanoma drug development. We believe that the union of these three approaches is essential to improving the timely development of novel melanoma treatments while minimizing the unnecessary use of laboratory animals.